A method for preparing vertical cavity laser by transferring perovskite film
By physically and mechanically transferring the perovskite polycrystalline film with a hydrophilic flexible substrate, the problem of insufficient optical resonance cavity length of the perovskite laser is solved, and the effect of increasing the cavity length without introducing optical loss is achieved, which expands the application of perovskite in the laser field.
Patent Information
- Application Number
- CN202210192256.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-03-01
AI Technical Summary
The optical resonance cavity length of existing perovskite lasers is insufficient, resulting in the inability to achieve lasing. The commonly used polymethyl methacrylate (PMMA) cushion introduces optical loss, affecting the performance of the laser.
By physically mechanically transferring the perovskite polycrystalline film with a hydrophilic flexible substrate, the thickness of the perovskite film between the DBR mirror substrate is increased, thereby increasing the cavity length of the vertical cavity laser.
The cavity length of the vertical cavity laser is increased without additional optical loss, which solves the problem of insufficient thickness of the low solubility perovskite film and expands its application in the laser field.
Smart Images

Figure CN114583553B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lasers, and in particular to a method for preparing a vertical cavity laser by transferring a perovskite film. Background Art
[0002] Organic-inorganic hybrid perovskite semiconductor materials have received extensive research attention in recent years. This type of material has excellent optoelectronic properties, such as direct bandgap semiconductor properties, large light absorption coefficient, high defect tolerance, high photoluminescence quantum yield, continuously adjustable bandgap, large exciton binding energy, etc., and its cost is lower than traditional semiconductors. Therefore, it is a type of laser gain medium material with huge commercial research value.
[0003] According to the structure, perovskite lasers are divided into vertical cavity surface emitting lasers (VCSEL), distributed feedback lasers (DFB), Fabry-Perot resonant cavity (FP), and whispering gallery mode cavity (WGM). Among them, the vertical cavity surface emitting laser is a type of laser structure with outstanding commercial application value because it is compatible with the planar process of existing commercial semiconductor lasers and is easy to realize patterned arraying. If the optical resonant cavity length (abbreviated as: optical cavity length, cavity length) of the vertical cavity surface emitting laser is too small, lasing cannot be achieved. Its cavity length is mainly determined by the thickness of the gain medium perovskite material.
[0004] The thickness of the perovskite polycrystalline film is mainly determined by the spin coating speed and the concentration of the precursor solution. On the one hand, the smaller the rotation speed, the thicker the film, but there is a critical value. When it is less than the critical value, the film quality deteriorates significantly and its photoelectric properties are affected. On the other hand, for some perovskite material systems with high optical gain but low solubility (for example: quasi-two-dimensional perovskite), due to the limitation of precursor solubility, the thickness of the spin-coated film cannot meet the optical resonant cavity length requirements of the vertical cavity laser.
[0005] A common method to increase the length of the optical resonant cavity of a vertical cavity laser is to spin-coat polymethyl methacrylate (PMMA) as a cushion layer in the resonant cavity. However, PMMA is a non-gain material, and its introduction will produce optical losses, which is not conducive to the optical performance of the laser device. Summary of the invention
[0006] In view of this, an object of the present invention is to provide a method for preparing a vertical cavity laser by transferring a perovskite thin film. The method of the present invention can increase the cavity length of the vertical cavity laser without introducing additional optical loss.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a vertical cavity laser by transferring a perovskite film, comprising the following steps:
[0009] (1) providing a first DBR reflector substrate spin-coated with a first perovskite polycrystalline thin film, a second DBR reflector substrate spin-coated with a second perovskite polycrystalline thin film, and a hydrophilic flexible substrate spin-coated with a third perovskite polycrystalline thin film;
[0010] (2) laminating the side of the hydrophilic flexible substrate on which the third perovskite polycrystalline film is spin-coated with the side of the first DBR reflector substrate on which the first perovskite polycrystalline film is spin-coated, applying pressure and removing pressure in sequence, uncovering the hydrophilic flexible substrate, and transferring the third perovskite polycrystalline film to the surface of the first perovskite film;
[0011] (3) The side of the second DBR reflector substrate on which the second perovskite polycrystalline film is spin-coated is bonded to the third perovskite polycrystalline film to obtain a vertical cavity laser.
[0012] Preferably, the first perovskite polycrystalline film, the second perovskite polycrystalline film, and the third perovskite polycrystalline film are independently quasi-two-dimensional perovskite polycrystalline films.
[0013] Preferably, the quasi-two-dimensional perovskite component is as shown in Formula I:
[0014] A2B n-2 PbX 3n+1 Formula I;
[0015] In formula I, A is one or more of phenylethylamine, butylamine, octylamine, 1-naphthylmethylammonium and diphenylphosphoryl azide;
[0016] B is one or more of cesium, methylamine and formamidine;
[0017] X is one or more of chlorine, bromine and iodine;
[0018] n≥2.
[0019] Preferably, the pressure applied in step (2) is 0.1 to 0.5 MPa, and the time for applying the pressure is 5 to 10 minutes.
[0020] Preferably, the method for preparing the hydrophilic flexible substrate spin-coated with the third perovskite polycrystalline thin film comprises:
[0021] Prepare a flexible material layer on the surface of the master substrate to obtain a flexible substrate;
[0022] Performing ozone-plasma treatment on the flexible substrate to obtain a hydrophilic flexible substrate;
[0023] The third perovskite is spin-coated on the surface of the hydrophilic flexible substrate, and after annealing, a hydrophilic flexible substrate spin-coated with the third perovskite polycrystalline film is obtained.
[0024] Preferably, the spin coating of the third perovskite includes low-speed spin coating and high-speed spin coating performed sequentially, the low-speed spin coating has a rate of 500-600 rpm and a time of 5-10 s, and the high-speed spin coating has a rate of 2000-7000 rpm and a time of 30-90 s.
[0025] Preferably, the annealing temperature is 50-120° C. and the time is 5-20 min.
[0026] Preferably, the thickness of the first perovskite polycrystalline thin film and the second perovskite polycrystalline thin film are independently 30 to 70 nm.
[0027] Preferably, the thickness of the third perovskite polycrystalline film is 30-70 nm, and the area of the third perovskite polycrystalline film after transfer is 0.01-1 cm 2 .
[0028] The invention provides a vertical cavity laser prepared by the above method, which comprises in sequence a first DBR reflector substrate, a first perovskite polycrystalline film, a third perovskite polycrystalline film, a second perovskite polycrystalline film and a second DBR reflector substrate.
[0029] The present invention provides a method for preparing a vertical cavity laser by transferring a perovskite film, comprising the following steps: (1) providing a first DBR reflector substrate spin-coated with a first perovskite polycrystalline film, a second DBR reflector substrate spin-coated with a second perovskite polycrystalline film, and a hydrophilic flexible substrate spin-coated with a third perovskite polycrystalline film; (2) laminating one side of the hydrophilic flexible substrate spin-coated with the third perovskite polycrystalline film with one side of the first DBR reflector substrate spin-coated with the first perovskite polycrystalline film, applying pressure, uncovering the hydrophilic flexible substrate, and transferring the third perovskite polycrystalline film to the surface of the first perovskite film; (3) laminating one side of the second DBR reflector substrate spin-coated with the second perovskite polycrystalline film with the third perovskite polycrystalline film to obtain a vertical cavity laser. The present invention utilizes a hydrophilic flexible substrate to perform physical and mechanical transfer of the perovskite polycrystalline film, and the transferred film has a large area and high flatness, and can increase the thickness of the perovskite film between the DBR reflector substrates, thereby increasing the cavity length of the vertical cavity laser. The method of physical and mechanical transfer of perovskite films using flexible substrates will not change their surface morphology and optical properties, and will not introduce additional optical losses. It can solve the problem that the film thickness of low-solubility perovskites is too small to meet the optical resonant cavity length, thereby expanding their application in the laser field.
[0030] At the same time, the method provided by the invention is simple to operate, low in cost, and easy to realize industrialized mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a flow chart of perovskite film transfer;
[0032] Figure 2 This is a schematic diagram of the structure of the vertical laser obtained in Example 1;
[0033] Figure 3 This is the actual picture of the perovskite polycrystalline film after transfer;
[0034] Figure 4 AFM characterization of perovskite polycrystalline films before and after transfer;
[0035] Figure 5 Optical micrographs of perovskite polycrystalline films after transfer and absorption and emission spectra before and after film transfer;
[0036] Figure 6 The photoluminescence spectra of the vertical cavity laser structure device without and after the film is transferred are compared;
[0037] Figure 7 This is the dependence of the half-width and peak intensity of the vertical cavity laser on the pump power;
[0038] Figure 8 is the dependence of the polarization degree of the vertical cavity laser on the pump power;
[0039] Fig. 9 The photoluminescence spectra of the vertical cavity laser structure device with variable pump power prepared without transferring the film and after transferring the film. DETAILED DESCRIPTION
[0040] The present invention provides a method for preparing a vertical cavity laser by transferring a perovskite film, comprising the following steps:
[0041] (1) providing a first DBR reflector substrate spin-coated with a first perovskite polycrystalline thin film, a second DBR reflector substrate spin-coated with a second perovskite polycrystalline thin film, and a hydrophilic flexible substrate spin-coated with a third perovskite polycrystalline thin film;
[0042] (2) laminating the side of the hydrophilic flexible substrate on which the third perovskite polycrystalline film is spin-coated with the side of the first DBR reflector substrate on which the first perovskite polycrystalline film is spin-coated, applying pressure, uncovering the hydrophilic flexible substrate, and transferring the third perovskite polycrystalline film to the surface of the first perovskite film;
[0043] (3) The side of the second DBR reflector substrate on which the second perovskite polycrystalline film is spin-coated is bonded to the third perovskite polycrystalline film to obtain a vertical cavity laser.
[0044] The present invention provides a first DBR reflector substrate spin-coated with a first perovskite polycrystalline film, a second DBR reflector substrate spin-coated with a second perovskite polycrystalline film, and a hydrophilic flexible substrate spin-coated with a third perovskite polycrystalline film. In the present invention, the first perovskite polycrystalline film, the second perovskite polycrystalline film, and the third perovskite polycrystalline film are independently preferably quasi-two-dimensional perovskite polycrystalline films. In the present invention, the composition of the quasi-two-dimensional perovskite is preferably as shown in Formula I:
[0045] A2B n-2 PbX 3n+1 Formula I;
[0046] In formula I, A is one or more of phenylethylamine, butylamine, octylamine, 1-naphthylmethylammonium and diphenylphosphoryl azide;
[0047] B is one or more of cesium, methylamine and formamidine;
[0048] X is one or more of chlorine, bromine and iodine;
[0049] n≥2.
[0050] More preferably, the quasi-two-dimensional perovskite is preferably one or more of cesium lead chloride bromide of phenethylamine, cesium lead chloride of phenethylamine, cesium lead chloride bromide of octylamine, cesium lead chloride bromide of octylamine, cesium lead chloride bromide of butylamine, cesium lead chloride bromide of butylamine, cesium lead chloride bromide of diphenyl phosphate azide, cesium lead chloride bromide of diphenyl phosphate azide, 1-naphthylmethylammonium cesium lead chloride bromide and 1-naphthylmethylammonium cesium lead chloride.
[0051] Quasi-two-dimensional perovskite is a natural multi-quantum well band structure with an energy funnel effect, and is a high-gain laser medium. One type of perovskite includes chlorine-based perovskites. Since the solubility of chlorine in organic solvents (for example, dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) is very low, the film thickness is much smaller than the minimum single-mode optical cavity length required by the vertical cavity laser while ensuring the high optical quality of the film. This limits the application of such high-gain materials in the field of lasers. The method for preparing a vertical cavity laser by transferring a perovskite film provided by the present invention solves the problem that the thickness of the quasi-two-dimensional perovskite film is too small to meet the optical resonant cavity length, and expands its application in the field of lasers.
[0052] In the present invention, the method for preparing the first DBR reflector substrate spin-coated with the first perovskite polycrystalline thin film preferably comprises the following steps:
[0053] Prepare a first DBR reflector layer on the surface of the substrate base;
[0054] A first perovskite polycrystalline thin film is spin-coated on the surface of the first DBR reflector layer, and after annealing, a first DBR reflector substrate spin-coated with the first perovskite polycrystalline thin film is obtained.
[0055] In the present invention, the substrate base is preferably a quartz substrate, a silicon substrate, a sapphire substrate or a mica substrate. The present invention has no special requirements for the method of preparing the first DBR reflector layer, and it can be prepared using a method well known to those skilled in the art.
[0056] In the present invention, the spin coating includes low-speed spin coating and high-speed spin coating performed sequentially, the speed of the low-speed spin coating is preferably 500-600 rpm, and the time is preferably 5-10 s; the speed of the high-speed spin coating is preferably 2000-7000 rpm, more preferably 2250-4000 rpm; the time is preferably 30-90 s, more preferably 50-80 s. In the present invention, the purpose of the low-speed spin coating is to improve the flatness of the film.
[0057] In the present invention, the annealing temperature is preferably 50 to 120° C., more preferably 90 to 110° C., and the annealing time is preferably 5 to 20 min, more preferably 10 to 15 min.
[0058] In the present invention, the preparation method of the second DBR reflector substrate spin-coated with the second perovskite polycrystalline film is the same as the preparation method of the first DBR reflector substrate spin-coated with the first perovskite polycrystalline film, which will not be repeated here.
[0059] In the present invention, the thickness of the first perovskite polycrystalline thin film and the second perovskite polycrystalline thin film are independently preferably 30 to 70 nm, and more preferably 40 to 60 nm.
[0060] In the present invention, the method for preparing the hydrophilic flexible substrate spin-coated with the third perovskite polycrystalline thin film preferably comprises the following steps:
[0061] Prepare a flexible material layer on the surface of the master substrate to obtain a flexible substrate;
[0062] Performing ozone-plasma treatment on the flexible substrate to obtain a hydrophilic flexible substrate;
[0063] The third perovskite is spin-coated on the surface of the hydrophilic flexible substrate, and after annealing, a hydrophilic flexible substrate spin-coated with the third perovskite polycrystalline film is obtained.
[0064] In the present invention, the master substrate is preferably a single crystal silicon substrate, a gallium nitride substrate, a quartz substrate, a glass substrate, a sapphire substrate or a mica substrate. In the present invention, the flatness of the master substrate is preferably at the atomic level.
[0065] In the present invention, the flexible material is preferably one or more of polydimethylsiloxane PDMS, polyethylene terephthalate PET, indium tin oxide ITO, polyethylene naphthalate PEN and silica gel. The present invention has no special requirements for the method of preparing the flexible material layer, and it can be prepared in a manner well known to those skilled in the art.
[0066] In the present invention, the power of the ozone-plasma treatment is preferably medium power, more preferably 10 to 15 W, and further preferably 12 to 14 W; the time of the ozone-plasma treatment is preferably 3 to 4 minutes. The present invention uses the ozone-plasma cleaning to bombard the surface of the flexible substrate with plasma to increase the surface energy of the substrate, so that the originally hydrophobic PDMS substrate surface can be made hydrophilic.
[0067] Within 30 minutes of obtaining a hydrophilic flexible substrate by ozone-plasma treatment, the present invention spin-coats the third perovskite on the surface of the hydrophilic flexible substrate. In the present invention, the spin coating of the third perovskite includes low-speed spin coating and high-speed spin coating performed sequentially, and the rate of the low-speed spin coating is preferably 500-600rpm, and the time is preferably 5-10s; the rate of the high-speed spin coating is preferably 2000-7000rpm, more preferably 2250-4000rpm; the time is preferably 30-90s, more preferably 50-80s. In the present invention, the purpose of the low-speed spin coating is to improve the flatness of the film.
[0068] In the present invention, the annealing temperature is preferably 50 to 120° C., more preferably 90 to 110° C., and the annealing time is preferably 5 to 20 minutes, more preferably 10 to 15 minutes. The present invention can improve the quality of perovskite crystals through the annealing treatment.
[0069] In the present invention, the thickness of the third perovskite polycrystalline thin film is preferably 30 to 70 nm, and more preferably 40 to 60 nm.
[0070] The present invention places the side of the hydrophilic flexible substrate on which the third perovskite polycrystalline film is spin-coated with the side of the first DBR reflector substrate on which the first perovskite polycrystalline film is spin-coated, applies pressure and removes pressure in sequence, uncovers the hydrophilic flexible substrate, and transfers the third perovskite polycrystalline film to the surface of the first perovskite film. In the present invention, the magnitude of the applied pressure is preferably 0.1 to 0.5 MPa, more preferably 0.2 to 0.4 MPa; the time for applying the pressure is preferably 5 to 10 minutes, more preferably 6 to 8 minutes.
[0071] After the pressure is removed, the flexible substrate is preferably quickly torn off from one end to complete the transfer of the third perovskite polycrystalline film. In the present invention, the area of the third perovskite polycrystalline film after transfer is preferably 0.01 to 1 cm 2, more preferably 0.8 cm 2 .
[0072] The present invention laminates the side of the second DBR reflector substrate on which the second perovskite polycrystalline film is spin-coated with the third perovskite polycrystalline film to obtain a vertical cavity laser. The present invention has no special requirements for the lamination method, and the operation method familiar to those skilled in the art can be used.
[0073] The invention provides a vertical cavity laser prepared by the above method, which comprises in sequence a first DBR reflector substrate, a first perovskite polycrystalline film, a third perovskite polycrystalline film, a second perovskite polycrystalline film and a second DBR reflector substrate.
[0074] The following is a detailed description of a method for preparing a vertical cavity laser by transferring a perovskite film provided by the present invention in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0075] Example 1
[0076] The vertical cavity laser based on quasi-two-dimensional perovskite polycrystalline thin film was prepared by large-area perovskite film transfer method through the following steps:
[0077] (1) The matrix and curing agent were mixed in a weight ratio of 10:1 and stirred for 5 minutes to fully mix. Then, the mixture was vacuumed for 30 minutes to completely remove the bubbles in the mixed solution. Then, atomically flat silicon was used as a substrate, the mixed solution was poured into it, and vacuumed again for 10 minutes. It was placed in an oven at 80°C for 1 hour to cure it, thereby preparing a large-scale PDMS (polydimethylsiloxane) flexible substrate.
[0078] (2) The prepared PDMS substrate is placed in an ozone-plasma instrument and operated at a medium power of 15 W for 3 minutes. The surface of the flexible substrate is bombarded with plasma to increase the surface energy of the substrate, thereby making the originally hydrophobic PDMS substrate surface hydrophilic.
[0079] (3) Within 30 minutes after the PDMS substrate was treated with ozone-plasma, a quasi-two-dimensional perovskite polycrystalline film (components: phenylethylamine, cesium, lead, chloride, and bromide) was spin-coated at 500 rpm for 5 s and 2250 rpm for 60 s and annealed at 100°C for 10 min to improve the quality of the perovskite crystal.
[0080] (4) Align the flexible PDMS substrate with the perovskite polycrystalline film spin-coated with the DBR reflector to be transferred (spin-coated with phenylethylamine cesium lead chloride bromide, spin coating speed 500 rpm 5s, 2250 rpm 60s), and apply a uniform pressure of 0.4 MPa. After maintaining the pressure for 8 minutes, remove the pressure and quickly peel off the PDMS flexible substrate from one end to complete the transfer of the perovskite film. The transfer flow chart is shown in Figure 1 .
[0081] (5) Another DBR reflector spin-coated with phenylethylamine cesium lead chloride bromide is bonded to the transferred perovskite film to obtain a vertical cavity laser, named device 1. The structural schematic diagram of the obtained vertical laser is shown in Figure 2 .
[0082] Figure 3 This is a picture of the actual object after the transfer of the perovskite polycrystalline film, where (a) is the width dimension diagram and (b) is the effective area dimension diagram. Figure 3 It can be seen that the method of the present invention can achieve the transfer of films with a length of nearly 1 cm, and the effective area of the transferred film can reach 0.8 cm 2 This is a large area in the transfer method of new semiconductor perovskite materials. Generally, the length size of perovskite transfer achieved by the transfer method is 1 to 100 μm.
[0083] Figure 4 The AFM characterization of the perovskite polycrystalline film before and after transfer, where (a) is the AFM image of the perovskite polycrystalline film before transfer, (b) is the AFM image of the perovskite polycrystalline film after transfer in step (4), and (c) is the change curve of the thickness and position of the perovskite polycrystalline film before and after transfer. Figure 4 As can be seen in (c), the film transfer method can significantly increase the film thickness.
[0084] Figure 5 The optical micrograph of the perovskite polycrystalline film after transfer and the absorption and emission spectra before and after the film transfer. (a) is the optical micrograph, and (b) is the absorption and emission spectra before and after the film transfer. Figure 5 It can be seen that the transferred film is very flat, and the absorption spectrum and photoluminescence spectrum peaks of the perovskite polycrystalline film before and after the transfer are almost consistent, which shows that the physical mechanical transfer method using a flexible substrate does not change the surface morphology and optical properties of the film itself.
[0085] A comparative experiment was set up to prepare a vertical cavity laser by omitting the thin film transfer method while ensuring the same device structure and preparation process.
[0086] A repeated experiment was set up. While ensuring the same device structure and preparation process, the above-mentioned thin film transfer method was repeated to prepare a vertical cavity laser, which was named Device 2.
[0087] Figure 6 The photoluminescence spectra of the vertical cavity laser structure device without and after the film is transferred are compared. (a) and (b) correspond to the vertical cavity laser structure device 1 and device 2, respectively. Figure 7 This is the dependence of the half-width and peak intensity of the vertical cavity laser on the pump power; Figure 8is the dependence of the polarization degree of the vertical cavity laser on the pump power. Figures 6 to 8 It can be seen that the vertical cavity laser prepared by the present invention can be successfully lased, and the vertical cavity laser prepared by the thin film transfer method is repeatable.
[0088] Fig. 9 The photoluminescence spectra of the vertical cavity laser structure device prepared without the transferred film and after the transferred film are changed with the pump power, where (a) is the vertical cavity laser prepared without the transferred film, and (b) is the vertical cavity laser structure device prepared after the transferred film. Fig. 9 It can be seen that the vertical cavity laser structure device prepared by the untransferred film of the present invention cannot lasing.
[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a vertical cavity laser by transferring a perovskite film, comprising the following steps: (1) providing a first DBR reflector substrate spin-coated with a first perovskite polycrystalline thin film, a second DBR reflector substrate spin-coated with a second perovskite polycrystalline thin film, and a hydrophilic flexible substrate spin-coated with a third perovskite polycrystalline thin film; (2) laminating the side of the hydrophilic flexible substrate on which the third perovskite polycrystalline film is spin-coated with the side of the first DBR reflector substrate on which the first perovskite polycrystalline film is spin-coated, applying pressure and removing pressure in sequence, uncovering the hydrophilic flexible substrate, and transferring the third perovskite polycrystalline film to the surface of the first perovskite film; (3) The side of the second DBR reflector substrate on which the second perovskite polycrystalline film is spin-coated is bonded to the third perovskite polycrystalline film to obtain a vertical cavity laser.
2. The method for preparing a vertical cavity laser by transferring a perovskite thin film according to claim 1, characterized in that: The first perovskite polycrystalline film, the second perovskite polycrystalline film, and the third perovskite polycrystalline film are independently quasi-two-dimensional perovskite polycrystalline films.
3. The method for preparing a vertical cavity laser by transferring a perovskite film according to claim 2, characterized in that: The quasi-two-dimensional perovskite component is shown in Formula I: A2B n-2 PbX 3n+1 Formula I; In formula I, A is one or more of phenylethylamine, butylamine, octylamine, 1-naphthylmethylammonium and diphenylphosphoryl azide; B is one or more of cesium, methylamine and formamidine; X is one or more of chlorine, bromine and iodine; n≥2。 4. The method for preparing a vertical cavity laser by transferring a perovskite film according to claim 1, characterized in that: The pressure applied in step (2) is 0.1-0.5 MPa, and the time for applying the pressure is 5-10 min.
5. The method for preparing a vertical cavity laser by transferring a perovskite film according to claim 1, characterized in that: The method for preparing the hydrophilic flexible substrate spin-coated with the third perovskite polycrystalline thin film comprises: Prepare a flexible material layer on the surface of the master substrate to obtain a flexible substrate; Performing ozone-plasma treatment on the flexible substrate to obtain a hydrophilic flexible substrate; The third perovskite is spin-coated on the surface of the hydrophilic flexible substrate, and after annealing, a hydrophilic flexible substrate spin-coated with the third perovskite polycrystalline film is obtained.
6. The method for preparing a vertical cavity laser by transferring a perovskite film according to claim 5, characterized in that: The spin coating of the third perovskite includes low-speed spin coating and high-speed spin coating performed sequentially, the low-speed spin coating has a rate of 500-600 rpm and a time of 5-10 s, and the high-speed spin coating has a rate of 2000-7000 rpm and a time of 30-90 s.
7. The method for preparing a vertical cavity laser by transferring a perovskite film according to claim 5, characterized in that: The annealing temperature is 50-120° C. and the annealing time is 5-20 min.
8. The method according to claim 1, characterized in that: The thickness of the first perovskite polycrystalline thin film and the second perovskite polycrystalline thin film are independently 30 to 70 nm.
9. The method for preparing a vertical cavity laser by transferring a perovskite film according to claim 1, characterized in that: The thickness of the third perovskite polycrystalline film is 30-70 nm, and the area of the third perovskite polycrystalline film after transfer is 0.01-1 cm 2 .
10. The vertical cavity laser prepared by the method for preparing a vertical cavity laser by transferring a perovskite film as described in any one of claims 1 to 9 comprises, in sequence, a first DBR reflector substrate, a first perovskite polycrystalline film, a third perovskite polycrystalline film, a second perovskite polycrystalline film and a second DBR reflector substrate.
Citation Information
Patent Citations
Method for preparing vertical cavity surface emitting laser by in-situ growth perovskite single crystal thin film, and vertical cavity surface emitting laser
CN110504618A
Quantum well device, perpendicular to layers forming laser
FR2741195A1